THE POSITION OF UNINCORPORATED BUSINESS ENTITIES IN INDONESIAN POSITIVE LAW - Hemas Widya Hanggari; Prasetyo (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2025)
Commanditaire Vennotschaap or often reffered to as CV is a buseiness entity that can be used as another option besides PT for business actors with small capital who want to open a business considering that the process of establishing a CV is not as complicated as the process of establishing a PT. The first objective of this study is to analyze the regulation of CV which is an unincorporated business entity. The second objective is to analyze the legal position of CV in conducting legal acts in Indonesia. This research is conducted with an empirical research model with a descriptive analysis approach and uses data collection methods through interviews. This is done to find out whether CV as a business entity is in accordance with existing regulations. The results of this study reveal first, that the regulations on CVs are regulated in the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 17 of 2018 concerning Registration of Commodity Partnerships, Firm Partnerships, and Civil Partnerships and the Commercial Code. Second, CV as a business entity that is not incorporated, can still perform various legal acts such as conducting sale and purchase agreements, cooperation agreements, and other legal acts because it has a deed of establishment. Commandiitaire Vennotschaap atau yang sering disebut sebagai CV merupakan badan usaha yang dapat dijadikan opsi lain selain PT bagi para pelaku usaha dengan modal yang tidak besar yang ingin membuka usaha mengingat proses pendirian CV tidak serumit proses pendirian PT. Tujuan pertama penelitian ini untuk menganalisis pengaturan tentang CV yang merupakan badan usaha yang tidak berbadan hukum. Tujuan kedua adalah untuk menganalisis kedudukan hukum CV dalam melakukan perbuatan hukum di Indonesia. Penelitian ini dilakukan dengan model penelitian empiris dengan pendekatan deskriptif analisis dan menggunakan metode pengumpulan data melalui wawancara. Hal ini dilakukan untuk mengetahui apakah CV sebagai badan usaha sudah bersesuaian dengan peraturan yang ada. Hasil penelitian ini mengungkapkan pertama, bahwa peraturan tentang CV diatur dalam Peraturan Menteri Hukum dan Hak Asasi Manusia Republik Indonesia No. 17 Tahun 2018 tentang Pendaftaran Persekutuan Komanditer, Persekutuan Firma, dan Persekutuan Perdata; dan Kitab Undang-Undang Hukum Dagang. Kedua, CV sebagai badan usaha yang tidak berbadan hukum, masih tetap bisa melakukan berbagai perbuatan hukum seperti melakukan perjanjian jual beli, perjanjian kerja sama, dan perbuatan hukum lainnya karena telah memiliki akta pendirian.